Induction of Tumor Necrosis Factor and Interleukin-6 mRNA in Human Cytotrophoblast Cells Exposed to Lipopolysaccharide. Issue 1 (1994) - Gonik, Bernard; Rachmilewitz, Jacob; Hochberg, Avraham; Goshen, Ran; de-Groot, Nathan
Abstract : Objective: The cytokines tumor necrosis factor (TNF) and interleukin-6 (IL-6) have previously been identified in placental tissue and are known to be mediators of infection-associated induction of the host immune system. This study was undertaken to better characterize the in vitro regulation of these cytokines in cytotrophoblast cells when challenged with the bacterial product lipopolysaccharide (LPS). Methods: Term placentas were freshly collected, digested with trypsin/DNase, and subjected to Percoll gradient centrifugation to isolate cytotrophoblasts. Either immediately or after overnight incubation, LPS (1 μg/ml) or media alone was added to the cell cultures for 0, 1, 2, 4, 8, 24, 48, and 72 h. Total cellular RNA was isolated by the guanidinium thiocyanate/cesium chloride methodology. RNA samples were run on 1% agarose-formaldehyde gels and subsequently transferred to nylon filters. Blots were hybridized with the appropriate P32-radiolabeled probe. Results: In non-LPS-treated cells, minimal amounts of TNF mRNA could be detected at zero time, or throughout the incubation periods. Conversely, LPS exposure resulted in detectable signal starting at 1 h and peaking at 2 h after the addition of LPS. Overnight incubation gave stronger TNF signals in the LPS stimulated cells, although the kinetics of this response remained similar to zero time exposure. IL-6 was likewise minimally expressed at zero time, although non-stimulated cell cultures demonstrated progressive increases in mRNA expression which was maximal at 16 h after plating. LPS further augmented the transcription of IL-6 mRNA, with peak signals seen at 4 h after LPS stimulation. Again, overnight incubation of the cytotrophoblasts increased baseline and LPS-induced IL-6 mRNA responses. Long-term constant exposure of cells to LPS did not demonstrate any evidence of prolonged signaling. LPS did not alter mRNA expression of the placental gene H19 or the oncogene FOS. Conclusions: These data demonstrate the induction of TNF and IL-6 mRNA in cytotrophoblast cells with LPS. These transcriptional events are kinetically distinct and short term in nature. Overnight incubation accentuates the TNF and IL-6 mRNA signal and allows for an augmented response to LPS.